Enhancing Functional and Structural Properties of Advanced Materials through Scandium-based Nanostructures: Applications in Ceramics, Thermoelectrics, Memory Devices, and High-Strength Alloys - Rakshit Sanwal (International Journal of Minerals, 2024)
This study explores the fabrication and properties of scandium-based nanostructured materials with applications in ceramics, glass, thermoelectric modules, switching devices, and strengthened alloys. Scandium oxide (Sc₂O₃) nanopowders were synthesized using precipitation techniques and subsequently sintered to create transparent ceramics with fine dispersion. Investigations into scandium-doped metallic glasses demonstrated enhanced plastic deformation, with notable tensile plasticity attributed to its unique nanoglass structure. A new scandium-doped thermoelectric material, ZnCdO, was also developed, showing superior stability and power efficiency at high temperatures, marking a significant advancement over traditional ZnO-based thermoelectric materials. Additionally, ultra-thin Al-Sc films were explored for their ferroelectric switching properties, revealing high potential for non-volatile memory applications. Finally, the microalloying of Al-Mg-Mn with Sc and Zr was studied in the context of friction stir welding, yielding a notable increase in mechanical strength through refined grain structure and nanoparticle reinforcement. These findings demonstrate scandium’s versatility as an additive for enhancing the structural and functional properties of advanced materials, supporting a wide range of applications in high-performance technologies.
Keywords: Ceramics; ferroelectric switching; high-strength alloys; metallic glass deformation; scandium-based nanomaterials; thermoelectric materials